Co-developing resources for better public understanding of Longitudinal Population Study Data and the Law - Campbell, Kirsteen; Chave, Sarah; Hill, Rosie; Docherty, Mhairi; Gregg, Michael; Turner, Emma; Evans, Katharine; Oakley, Jacqui; McLachlan, Stela; Bailey, Alex; Smith, Cassie; Whitehorn, Rebecca; et al. (International Journal of Population Data Science, 2025)
Introduction The legal basis for using participants' data in Longitudinal Population Studies (LPS) is complex. Laws of particular relevance are (1) UK data protection legislation, including Data Protection Act 2018 and UK General Data Protection Regulation (UK-GDPR); (2) common law duty of confidentiality; (3) Digital Economy Act (DEA) 2017; (4) Section 251 of the National Health Service Act 2006; and (5) Health Service (Control of Patient Information) Regulations 2002. Objective To develop transparency materials for LPS participants to raise awareness and understanding of key laws, legal principles and their rights. Methods Public contributors from UK Longitudinal Linkage Collaboration (UK LLC), Health Data Research UK (HDR UK) and DATAMIND provided input to benchmark current public understanding of laws and legal principles relevant to research. Based on this involvement, we worked with the UK LLC Public Advisory Group (PAG) and external organisations to produce a series of infographics. These were available in written English, audio, British Sign Language (BSL) and additional languages, to reach as wide an audience as possible. Results Input from 56 public contributors informed the work by suggesting low levels of awareness of the laws and legal principles. The DEA was the least well-known, with 11% of people aware of this legislation and the most well-known was UK-GDPR, with 88% awareness. We developed key messages for LPS participants on what they should be aware of as individuals, including what they should expect from their LPS. The information is available to the public and LPS participants as a series of infographics (https://ukllc.ac.uk/lps-data-and-the-law). Conclusion Our series of transparency materials support LPS participants to understand the legal basis for study data use, and their rights. General awareness of the laws and legal principles involved in the use of longitudinal data is low and we recommend data providers should raise awareness in clear and accessible ways.